ANALISIS DAMPAK PROSES PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 PADA MAHASISWA PGSD FKIP UNIVERSITAS RIAU - Rahma Eka Rahma Putri; Zufriady Zufriady; Eva Astuti Mulyani (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2022)
This study aims to describe the impact of online learning during the Covid-19 pandemic on pre-service elementary teachers, Riau University. This study uses descriptive quantitative research method. The population is 360 pre-service elementary teachers from PGSD FKIP Riau University, and the sample was 78 pre-service elementary teachers. For the data collection, a questionnaire filled out online using a google form. The questionnaire used a Likert scale. Data processing in the form is indicator of the impact of online learning during the Covid-19 pandemic. The indicators are facilities and infrastructure, independent and active, connected, and structured and systematic. Based on the results of the study, the score in the four indicators of the impact of online lectures which on; the facilities and infrastructure indicator got a percentage of 66.48%; the independent and active indicator the percentage of 69.87%; the connectedness indicator the percentage of 75 61%, and the last indicator of structured and systematic, got a percentage of 65.75%. This means that pre-service elementary teachers of Riau University had the impact of the online learning.